A novel approach for enhancement of coercivity in magnetic cobalt ferrite nanocrystal without applying post annealing. Issue 15 (15th November 2016) - Safi, Rohollah; Ghasemi, Ali; Shoja-Razavi, Reza
Abstract: Cobalt ferrite nano-crystals were synthesized by a low temperature co-precipitation method without post-annealing. In this work, size-controlled CoFe2 O4 was achieved by systematically tailoring the supersaturation condition during the nucleation and crystal growth processes. For this purpose, the effect of temperature, pH, and flow rate of addition of reactant solutions were evaluated. X-ray diffraction analysis (XRD), field emission scanning electron microscope (FE-SEM), and vibrating sample magnetometer (VSM) were carried out at room temperature to study the structural and magnetic properties of nanoparticles. M–H measurements verified the strong influence of synthesis conditions on the particle size and consequence magnetic properties of ferrite nanoparticles. The coercivity values up to 2029 Oe was obtained under optimum synthesis conditions.